Gender and Non-Normative Sex in Sub-Saharan Africa - Bond, Johanna (2016)
This Article argues for the adoption of a gender-based framework to supplement rights promotion strategies and campaigns based on LGBTI identity. The Article draws upon feminist, queer, and trans theory to develop an expansive understanding of gender within international human rights law. An analysis incorporating such theory will catalyze more systematic promotion of LGBTI rights. Although the approach is applicable across a variety of geographic contexts, this Article uses sub-Saharan Africa as an illustrative case study. A focus on gender rights as supplementary to and interrelated with LGBTI rights offers both conceptual and pragmatic benefits in the struggle to promote LGBTI rights in the region. Specifically, the United Nations Committee on the Elimination of Discrimination Against Women (CEDAW Committee) has failed to meaningfully and systematically address discrimination and violence directed at LGBTI communities in this region. An expansion of the CEDAW Committee’s interpretation of gender would encourage the Committee to consider rights violations perpetrated against those who do not conform to gender norms, including normative expressions of masculinity and femininity. First, a focus on non-normative gender expression and sexuality expands our understanding of affected individuals from only self-identified gays and lesbians to include those who do not necessarily identify as gay or lesbian but who, nevertheless, do not conform to traditional norms of sexuality and gender expression. Second, a gender framework facilitates intersectional analysis. If adopted, this analysis would allow the CEDAW Committee to more fully explore how race, ethnicity, and nationhood construct sexuality in the post-colonial period. Intersectional analysis would also allow the Committee to capitalize on its success in raising awareness about and combating gender-based violence. Finally, a gender framework offers the CEDAW Committee and U.N. treaty bodies a discursive wedge to open conversations about sexuality, even in places with wide-spread homophobia